BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP PERILAKU KERJA AMAN (SAFETY BEHAVIOR) PETANI TEMBAKAU DI KABUPATEN TEMANGGUNG - Yuyun Risqa Puspitasari; Syamsulhuda BM; Kusyogo Cahyo (Jurnal Kesehatan Masyarakat (Undip), 2019)
Temanggung Regency is one of the biggest tobacco producer in Indonesia. Hence, the number of tobacco farmers there are huge. Economically, the large number of tobacco production makes some benefits for tobacco farmers yet it causes occupational diseases such as pesticide poisoning (40,8%) and Green Tobacco Sickness (63,7%). Those diseases can be prevented or minimized by practicing safety behavior including personal protective equipment (PPE) use and personal hygiene practice. This study aimed to analyze the factors that influenced tobacco farmers’ safety behavior practice. The research used cross sectional study design. The populations were tobacco farmers in Temanggung Regency. Samples were selected by using multi stage random sampling and 150 were obtained. The data were analyzed by using univariate, bivariate, and multivariate analysis. The result showed that most of the respondents didn’t do safety behavior (66,0%) while working. The chi- square test showed perception of benefit (p=0,025), perception of barriers (p=0,001), self efficacy (p=0,000), and family support (p=0,000) have a significant correlation with tobacco farmers’ safety behavior. Multivariat analysis resulted that the most influencing factors toward tobacco farmers’ safety behavior was family support (p-value=0,000, OR=6,990). More in-depth and specific research related to safety behavior in each phase of tobacco production, increasing network of farmer groups, and making “safety practice” plan in tobacco farming is needed.